Taking snapshots of a moving electron wave packet in molecules using photoelectron holography in strong-field tunneling ionization - He, Mingrui; Fan, Yang; Zhou, Yueming; Lu, Peixiang (Chinese physics B, 2021)
Coherent superposition of electronic states induces attosecond electron motion in molecules. We theoretically investigate the strong-field ionization of this superposition state by numerically solving the time-dependent Schrödinger equation. In the obtained photoelectron momentum distribution, an intriguing bifurcation structure appears in the strong-field holographic interference pattern. We demonstrate that this bifurcation structure directly provides complete information about the status of the transient wave function of the superposition state: the horizontal location of the bifurcation in the momentum distribution reveals the relative phase of the involved components of the superposition state and the vertical position indicates the relative coefficient. Thus, this bifurcation structure takes a snapshot of the transient electron wave packet of the superposition state and provides an intuitive way to monitor electron motion in molecules.